Overexpression of a Phosphate Starvation Response AP2/ERF Gene From Physic Nut in Arabidopsis Alters Root Morphological Traits and Phosphate Starvation-Induced Anthocyanin Accumulation - Chen, Yanbo; Wu, Pingzhi; Zhao, Qianqian; Tang, Yuehui; Chen, Yaping; Li, Meiru; Jiang, Huawu; Wu, Guojiang (Frontiers in Plant Science, 2018)
Physic nut (Jatropha curcas L.) is highly tolerant of barren environments and a significant biofuel plant. To probe mechanisms of its tolerance mechanisms, we have analyzed genome-wide transcriptional profiles of 8-week-old physic nut seedlings subjected to Pi deficiency (P−) for 2 and 16 days, and Pi-sufficient conditions (P+) controls. We identified several phosphate transporters, purple acid phosphatases, and enzymes of membrane lipid metabolism among the 272 most differentially expressed genes. Genes of the miR399/PHO2 pathway (IPS, miR399, and members of the SPX family) showed alterations in expression. We also found that expression of several transcription factor genes was modulated by phosphate starvation stress in physic nut seedlings, including an AP2/ERF gene (JcERF035), which was down-regulated in both root and leaf tissues under Pi-deprivation. In JcERF035-overexpressing Arabidopsis lines both numbers and lengths of first-order lateral roots were dramatically reduced, but numbers of root hairs on the primary root tip were significantly elevated, under both P+ and P− conditions. Furthermore, the transgenic plants accumulated less anthocyanin but had similar Pi contents to wild-type plants under P-deficiency conditions. Expression levels of the tested genes related to anthocyanin biosynthesis and regulation, and genes induced by low phosphate, were significantly lower in shoots of transgenic lines than in wild-type plants under P-deficiency. Our data show that down-regulation of the JcERF035 gene might contribute to the regulation of root system architecture and both biosynthesis and accumulation of anthocyanins in aerial tissues of plants under low Pi conditions.